THE « EMPEROR» OF GERMAN GYNECOLOGISTS AND OBSTETRICIANS - J. W. Dudenhausen (IRBIS LLC, 2018)
The article highlights the main stages of life and work of the outstanding specialist in female diseases - German obstetrician, gynecologist, surgeon, scientist Walter Stoeckel.